2012
DOI: 10.1111/j.1369-1600.2012.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic inhibition of cocaine seeking in rats

Abstract: Inhibitory optogenetics was used to examine the roles of the prelimbic cortex (PL), the nucleus accumbens core (NAcore) and the PL projections to the NAcore in the reinstatement of cocaine seeking. Rats were microinjected into the PL or NAcore with an adeno-associated virus containing halorhodopsin or archaerhodopsin. After 12 days of cocaine self-administration, followed by extinction training, animals underwent reinstatement testing along with the presence/absence of optically induced inhibition via laser li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
191
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 6 publications
16
191
1
Order By: Relevance
“…Thus, optogenetic tools may be utilized to study the effects of specific ions on specific physiological processes. If side effects from the ions conducted by specific opsins are a concern, one useful strategy is to use multiple opsins that result in similar voltage effects, but rely on different ionic species (Adesnik et al 2012;Stefanik et al 2012;Kimura et al 2013). …”
Section: Channel and Pump Activitymentioning
confidence: 99%
“…Thus, optogenetic tools may be utilized to study the effects of specific ions on specific physiological processes. If side effects from the ions conducted by specific opsins are a concern, one useful strategy is to use multiple opsins that result in similar voltage effects, but rely on different ionic species (Adesnik et al 2012;Stefanik et al 2012;Kimura et al 2013). …”
Section: Channel and Pump Activitymentioning
confidence: 99%
“…Verification of optic probes' placement was performed with a standard Nissl stain preparation (Cresyl violet) and light microscopy according to the Paxinos and Watson atlas (2005). Expression in the cell bodies and axons in the VH was verified using immunohistochemistry procedures, as described previously Stefanik et al 2013). GFP/ eYFP expression was assessed using a light microscope.…”
Section: Verification Of Opsin Expression and Histologymentioning
confidence: 99%
“…Preclinical studies, eg, have demonstrated that optogenetic modulation of these mesolimbic and mesocortical circuits can modulate drug-taking behavior in a causal manner (Chen et al, 2013c;Stefanik et al, 2013). Clinical studies are now investigating repetitive TMS (rTMS) as a tool to change drug-craving and drug-taking behavior.…”
Section: Implications For Treatment Development-dorsal Medial and Latmentioning
confidence: 99%